2020
DOI: 10.1016/j.jfca.2020.103418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of management system and lactation stage on fatty acid composition of camel milk

Abstract: This study aimed to investigate the impact of management system and lactation stage on camel milk fatty acid (FA) composition, with emphasis on odd and branched-chain FA (OBCFA), conjugated linoleic acids (CLA), and trans-FA (TFA). Milk samples were collected from thirteen camels managed under intensive and semi-intensive systems at early, mid, and late lactation. Our results provided for the first time the OBCFA profile in camel milk. Eleven OBCFA were identified with a predominance of C15:0, anteiso-C15:0, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…Another aspect of explaining the reported blood lipid-lowering effect of CM is the presence of conjugated linoleic acid (CLA), which enhances the ratio of plasma LDL to HDL via reducing TG levels [ 58 ]. The CLA in CM ranges between 1.2 and 1.5% of the total fat content and varies depending on the source, diet, stage of lactation, and management system [ 59 ]. These differences may play a role in the variations in responses of patients with diabetes to the consumption of CM and the outcomes on blood lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of explaining the reported blood lipid-lowering effect of CM is the presence of conjugated linoleic acid (CLA), which enhances the ratio of plasma LDL to HDL via reducing TG levels [ 58 ]. The CLA in CM ranges between 1.2 and 1.5% of the total fat content and varies depending on the source, diet, stage of lactation, and management system [ 59 ]. These differences may play a role in the variations in responses of patients with diabetes to the consumption of CM and the outcomes on blood lipids.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major changes in camel milk production in recent decades is the emergence of intensive dairy farming systems characterized by an end to herd mobility (Chamekh et al, 2020). Central Asian countries in the Soviet era and now Gulf countries have been pioneers in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, camel milk contained higher levels of n-3 PUFAs compared to other livestock and was considered a functional food for the human diet [46]. In addition, the difference in lipid composition can be explained mainly by the different feeding conditions and camel breeds [47]. It has been demonstrated that camel milk from East Africa contained more fat than samples from Western Asia [10].…”
Section: Lipidsmentioning
confidence: 99%